Railway management : an evaluation of management cybernetics in a public enterprise - Paradissopoulos, Iordanis K. (Cranfield University, 1989)
Two are the objectives of this thesis: To identify structural and cultural causes of ineffectiveness in a state-owned railway enterprise in the light of the management cybernetics area of knowledge. To assess the capacity of this area of knowledge, especially in its abstract and coded form (Beer's Model of the Viable System), to provide adequate explanations of organizational performance and organizational failure. The objectives are sought in the analysis of an actual enterprise, the Greek Railways Organization (OSE). An 'ethnographic type' pilot study is initially undertaken, to highlight organizational problems under a management cybernetics perspective. The study, though demonstrating structural problems associated with a certain organizational culture, is assumed in itself inadequate, as it reflects a subjective interpretation of reality. A 'survey within the case study' is therefore undertaken aiming at deriving the real dimensions of organizational problems from an analysis of managerial responses. Responses are designed to provide a picture of both the actual way in which the enterprise organizes in the pursuit of its tasks, and the organizational culture. The first subtheme (organizational structure) is examined in terms of the cybernetic model of the viable organization. The findings, in general, validate the assumptions of the ethnographic study. Numerous structural problems are identified. The second subtheme (culture) is examined in terms of managerial cohesiveness, defined as the agreement between managers on key issues of the identity of the enterprise. The overall conclusion is that though managers are, in general, in agreement, the content of this agreement tends rather to reflect a shared pessimistic view of the future than cohesiveness facilitating viability and development. The conclusion, as regards the enterprise, is, that though many problems are reflected in the organizational structure, proper modifications of this structure may not suffice to guarantee improved performance, unless considerable attention is paid in the building of a relevant organizational culture, quite difficult under the specific circumstances. The conclusion, as regards the adopted methodology, is that though Beer's model of the viable system assists in a diagnosis of many organizational deficiencies, it may not suffice to promote organizational change, especially when narrowly perceived, i. e., when results to a concentration on structural arrangements in the expense of the building of a corporate culture. Certain methodologies should develop, which, while making use of the advantages of the model, will not underestimate other significant aspects of organizational reality.